Differences in platelet–leukocyte aggregates among subtypes of acute cerebral ischemia - Turgut, Burhan; Turgut, Nilda; Çelik, Yahya; Tekgündüz, Emre; Pamuk, Gülsüm Emel; Demir, Muzaffer (Journal of the neurological sciences, 2011)
Acute cerebral ischemia is caused by different pathophysiological mechanisms. The role of platelets and other blood cells can be different among the stroke subtypes. Seventy-two patients with acute ischemic cerebrovascular disease, including 31 patients with large vessel disease, 21 patients with cardioembolic disease, and 20 patients with small vessel disease, were evaluated. P-selectin (CD62P) expression and platelet leukocyte aggregates were measured with flow cytometry at the acute phase after the ischemic event. Markers were also measured in 37 control subjects. In all subjects, the serum high-sensitivity C-reactive protein (CRP) was also measured. The platelet-monocyte aggregates (PMA) and platelet-granulocyte aggregates (PGA) in the large vessel disease group were higher than in control group (P = 0.002, and P < 0.0001, respectively). The PMA and PGA in the small vessel disease group were also higher than in the control group (P = 0.004 and P < 0.0001, respectively). In contrast, in the cardioembolic disease group, the PMA and PGA were not significantly different from the control group. CD62P expression was higher in all of the patient groups relative to the control group (P < 0.05 for all comparisons). Serum CRP levels were also higher in all of the patient groups than in the control group (P < 0.0001 for all comparisons). In contrast to large vessel and small vessel disease, it seems that platelet–leukocyte association does not play a crucial role in the pathogenesis of cardioembolic stroke.